Complications of Halo Vest Orthosis: A Narrative Study - Ali Babashahi; Majid Rezvani; Majid Vatankhah; Navid Kalani; Ali Kazeminezhad (Iranian Journal of Neurosurgery, 2021)
Background and Aim: Perry and Nickel introduced the halo vest in 1959. It is the most common immobilization device for the unstable cervical spine. In the literature review, most articles review the beneficial effects of the halo vest, and a few report its complications. This study aims to evaluate the complications associated with halo orthosis. Methods and Materials/Patients: This is a narrative study about halo vest complications. To provide up-to-date information, we reviewed the articles written about halo complications. All relevant articles were retrieved from Google Scholar, Medline, PubMed, etc., using the keywords of “halo vest orthosis”, “unstable cervical spine fracture”, “halo vest complications”, “halo vest immobilization”, “pin-site-related complications”, and “vest-related complications”. Afterward, we reviewed and critically analyzed the articles. Results: At first, the halo vest was used for postoperative paralyzed poliomyelitis patients, and later, it was also used for traumatic injury of the cervical spine or postoperatively in cervical spine reconstructive surgery. Compared to other orthoses, the halo vest provides a more effective external fixation and maintains normal anatomic alignment of the cervical spine without impacting jaw motion and resulting in eating problems. However, it has many temporary complications. To prevent halo vest complications, experienced people should apply it, and the patients should be regularly followed up for early detection and treatment of complications. Conclusion: Our review is the starting point for the evaluation and investigation of halo vest complications. Because of the high incidence of pin loosening and infection, it is better to evaluate the design and application of halo pin. Since the initial design of the halo vest, only its superstructure has been redesigned without any significant change in other parts of it.